Conversion of Bivalve Shells to Monocalcium and Tricalcium Phosphates: An Approach to Recycle Seafood Wastes - Somkiat Seesanong; Banjong Boonchom; Kittichai Chaiseeda; Wimonmat Boonmee; Nongnuch Laohavisuti (My University, 2021)
The search for sustainable resources remains a subject of global interest and the conversion of the abundantly available bivalve shell wastes to advanced materials is an intriguing method. By grinding, calcium carbonate (CaCO3) powder was obtained from each shell of bivalves (cockle, mussel, and oyster) as revealed by FTIR and XRD results. Each individual shell powder was reacted with H3PO4 and H2O to prepare Ca(H2PO4)2·H2O giving an anorthic crystal structure. The calcination of the mixture of each shell powder and its produced Ca(H2PO4)2·H2O, at 900 °C for 3 h, resulted in rhombohedral crystal β-Ca3(PO4)2 powder. The FTIR and XRD data of the CaCO3, Ca(H2PO4)2·H2O, and Ca3(PO4)2 prepared from each shell powder are quite similar, showing no impurities. The thermal behaviors of CaCO3 and Ca(H2PO4)2·H2O produced from each shell were slightly different. However, particle sizes and morphologies of the same products obtained from different shells were slightly different—but those are significantly different for the kind of the obtained products. Overall, the products (CaCO3, Ca(H2PO4)2·H2O, and Ca3(PO4)2) were obtained from the bivalve shell wastes by a rapidly simple, environmentally benign, and low-cost approach, which shows huge potential in many industries providing both economic and ecological benefits.
Keywords: Calcium Carbonate Crystallization and Inhibition